Emergence of Azoles Resistance Candida species in Iranian AIDS defined patients with oropharyngeal candidiasis - Farzad Katiraee; Fardis Teifoori; Mino Soltani (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Oropharyngeal candidiasis (OPC) and antifungal drug resistance are major health concerns in patients with human immunodeficiency virus (HIV). The increased reports of antifungal resistance and expanding drug therapy options prompted the determination of antifungal susceptibility profile. The present study was performed to determine the antifungal susceptibility of Candida species isolated from AIDS patients with OPC in Iran. Materials and Methods: In total, 100 Candida isolates from the oral cavity of patients with OPC (TCD4 < 200 cells/&muL) were obtained and cultured on CHROMagar and Sabouraud's dextrose agar. All isolates were identified according to the assimilation profile, colony color and other conventional methods. Broth microdilution of antifungal drugs was carried out, according to the methods described in M27-S4 and M44-A guidelines by the Clinical and Laboratory Standards Institute (CLSI). Results: Among 60 Candida albicans (C. albicans) strains, 56.7% were resistant to fluconazole, while 38.3% were resistant to ketoconazole and clotrimazole. The resistance of C. albicans isolates against polyene antifungals including amphotericin B was scarce (1.7%). Based on the results, 52.2% of C. glabrata strains were resistant to fluconazole, while 47.8% and 30.4% of these isolates were resistant to ketoconazole and clotrimazole, respectively. All Candida isolates were susceptible to nystatin and caspofungin. Conclusion: Based on the findings, it can be concluded that screening of resistant Candida isolates by disk diffusion or broth dilution method is essential for the surveillance and prevention of antifungal resistance in patient management. Although nystatin is widely used in clinical practice for HIV patients in Iran, no evidence of enhanced resistance against this agent was found on the other hand, resistance to azole antifungals, particularly fluconazole, increased. Considering the lack of resistance to caspofungin, administration of this agent is suggested for the treatment of OPC in AIDS patients.